(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article examines the analysis of the process of competitive activity of martial artists, substantiation of the content of the system of control of physical fitness, condition and operational decision-making of athletes in the process of competitions. The theoretical validity of the issue under consideration is confirmed by the research of many scientists.